Intertemporal Substitution in Consumption Revisited - Hu, Zuliu (Washington, D.C. : International Monetary Fund, 1993)
Some of the highly controversial questions in macroeconomics critically hinge on the value of a single parameter of consumer preference--the elasticity of intertemporal substitution. This paper provides new estimates of this parameter for individual G-7 and a panel of twenty OECD countries. We find that single equation GMM estimates are typically small and imprecise, consistent with Hall's (1988) finding from the U.S. data. Estimation of a system of equations that takes into account the cross-equation restrictions implied by theory, however, generally gives larger and better determined values for the parameter. The panel procedure also yields relatively large estimates. Overall our multi-country results contradict the hypothesis of zero intertemporal substitution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet